Science and Social Inequality : Feminist and Postcolonial Issues - Harding, Sandra G. (Book collections on Project MUSE., 2006)
"In Science and Social Inequality, Sandra Harding makes the provocative argument that the philosophy and practices of today's Western science, contrary to its Enlightenment mission, work to insure that more science will only worsen existing gaps between the best and worst off around the world. She defends this claim by exposing the ways that hierarchical social formations in modern Western sciences encode antidemocratic principles and practices, particularly in terms of their services to militarism, the impoverishment and alienation of labor, Western expansion, and environmental destruction. The essays in this collection--drawing on feminist, multicultural, and postcolonial studies--propose ways to reconceptualize the sciences in the global social order. At issue here are not only social justice and environmental issues but also the accuracy and comprehensiveness of our understandings of natural and social worlds. The inadvertent complicity of the sciences with antidemocratic projects obscures natural and social realities and thus blocks the growth of scientific knowledge. Scientists, policy makers, social justice movements and the consumers of scientific products (that is, the rest of us) can work together and separately to improve this situation."--